Occurrence, characterization and management of fruit rot of immature cucumber fruits under arid greenhouse conditions - AL-SADI, ABDULLAH; AL-SAID, FAHAD; AL-KAABI, SIAF; AL-QURAINI, SUAD; AL-MAZROUI, SAFA; AL-MAHMOOLI, ISSA; DEADMAN, MIKE (Phytopathologia Mediterranea, 2012)
A study was undertaken to characterize and manage pathogens associated with fruit rot of immature cucumber fruits in greenhouses in Oman. A survey over 5 growing seasons from 2008 to 2010 in 99 different greenhouses in Oman showed that the disease is prevalent in 91 (92%) greenhouses and results in losses of 10 to 60% (avg. 33%) of immature fruits per plant. Incidence of the disease was not found to be affected by growing seasons, which could be attributed to the limited fluctuations in ambient temperatures in greenhouses. Isolations from diseased cucumber fruits yielded Alternaria alternata (isolation frequency = 52%), Fusarium equiseti (40%), Cladosporium tenuissium (27%), Botrytis cinerea (6%), Fusarium solani (6%), Corynespora cassiicola (3%), Aspergillus spp. (2%), Curvularia sp. (1%) and Bipolaris sp. (1%). With the exception of Curvularia and Bipolaris species, all other fungi were pathogenic on cucumber fruits, with Fusarium equiseti being the most aggressive, followed by Corynespora cassiicola, Botrytis cinerea and Alternaria alternata. Cladosporium and Aspergillus spp. were found to be weakly pathogenic. Comparing the efficacy of foliar and soil applications of carbendazim fungicide on fruit rot of cucumber showed that foliar applications significantly reduced fruit rot and increased cucumber yield when compared to soil application or to control (P < 0.01). This appears to be the first report of the association of Corynespora cassiicola and Fusarium equiseti with fruit rot of immature greenhouse cucumbers. This is also the first report in Oman for the association of Cladosporium tenuissimum with fruit rot of immature cucumbers. Findings are discussed in terms of factors affecting disease control in greenhouses using carbendazim.